Asbestosis and the Serratus Anterior Muscle - Collins, James D. (1983)
Twenty-seven patients with a history of asbestos exposure were reviewed at the UCLA Medical Center in December 1981. All patients were referred by the United States Department of Labor. The patients were told they had asbestosis on the basis of their history of exposure and chest radiographs taken at a local asbestos screening program and initially interpreted by a “B” reader. None of the 27 patients reviewed were found to have evidence of asbestosis either clinically or radiographically. The false-positive radiographic interpretations were due to the extrathoracic musculature (serratus anterior) mimicking intrathoracic disease. Since the study described here was done, an additional 330 patients have had their radiographs reviewed.